2007
DOI: 10.1016/j.jcrs.2007.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endothelial changes in phakic eyes after Artisan intraocular lens implantation to correct myopia

Abstract: Continuous endothelial cell loss was observed after surgery during a 5-year follow-up, especially during the first 2 years. A decrease in the coefficient of variation and an increase in the percentage of hexagonal cells were observed over time, reflecting the increasing stability and remodeling of the corneal endothelial cells 5 years postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 35 publications
5
54
0
4
Order By: Relevance
“…Several studies of Artisan iris-fixated IOL implantation have reported endothelial damage and cell loss. 6,7 Consistent with previous reports on phakic and aphakic eyes, [6][7][8] Artisan IOLs in our study induced a mean corneal endothelial cell loss of 8.1% in first 6 months of follow-up. Some limitations of our study were short follow-up for ECD measurements, and lack of data about other important parameters like coefficient of variation and percentage of hexagonal cells.…”
Section: Complicationssupporting
confidence: 92%
See 2 more Smart Citations
“…Several studies of Artisan iris-fixated IOL implantation have reported endothelial damage and cell loss. 6,7 Consistent with previous reports on phakic and aphakic eyes, [6][7][8] Artisan IOLs in our study induced a mean corneal endothelial cell loss of 8.1% in first 6 months of follow-up. Some limitations of our study were short follow-up for ECD measurements, and lack of data about other important parameters like coefficient of variation and percentage of hexagonal cells.…”
Section: Complicationssupporting
confidence: 92%
“…Endothelial cell loss of 10.3% in aphakic eyes with sutured fixated PCIOL implantation was reported. 21 Cell loss occurred predominantly during the first year 7 ; however, continuous endothelial cell loss was observed previously after Artisan implantation 7,8 as well as PCIOL. 22 Although the distance between IOL and endothelium is more adequate in aphakic cases, there is likely more movement or IOL donesis than phakic eyes.…”
Section: Complicationsmentioning
confidence: 73%
See 1 more Smart Citation
“…1 Artisan phakic IOLs have been demonstrated to be a safe option with respect to endothelial cell count, with a reported loss between 8.6% and 14.5% at 5 years. [8][9][10] In our case, the preoperative deep anterior chamber (3.96 mm) and the resultant postoperative critical distances (the distances between the optic edges of the phakic IOL and the corneal endothelium) of 1.71 mm and 2.11 mm (Figure 1) provided a safeguard against endothelial cell loss. 11 The preoperative and 1 year postoperative endothelial cell counts were 2043 cells/mm 2 and 1827 cells/mm 2 , respectively (10.6% cell loss).…”
Section: Discussionmentioning
confidence: 61%
“…No loss of BCVA occurred but reported complications included iris atrophy in 11.8% and night glare in 6.4%. In a 5-year follow-up study of 49 highly myopic eyes of 30 patients, Benedetti et al [15] reported progressive endothelial cell loss ranging from 2.3% 4 months postoperatively to 9% at 5 years. An increase in hexagonal cells and reduction in coefficient of variation over time was found, reflecting increasing stability and remodelling of the corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 99%